LONTAR SAMADHI GEGELARAN WIKU DITINJAU DARI SEGI PENDIDIKAN - I Wayan Darna (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2023)
The purpose of this study was to find out (1) how the teachings of Semadhi Yoga are used as Spiritual Education 2) How the Teachings of Samadhi Yoga are as Ethical Education for Wiku. 3) How are the teachings of Samadhi Yoga as a means to form a complete human being. How are the Teachings of Samadhi Yoga Gegelaran as a means to achieve educational goals. Data collection is done by technique document study, observation, literature study, and interviews. Furthermore The collected data were analyzed using qualitative descriptive analysis techniques using the Miles and Huberman analysis model with steps (1) data reduction, (2) data presentation, and (3) drawing conclusions. The presentation of the results of data analysis was carried out using informal techniques, namely use a narrative or descriptive form. The results of this study shows that 1. The Teachings of Samadhi Yoga Gegelaran as a means to achieve educational goals The teachings of Samadhi Yoga contained in the Lontar Samadhi Yoga Gegelaran Wiku were indeed prepared by the compilers to educate spiritually for Wiku who have undergone the diksa ceremony. In the teachings of the Vedas and the teachings of the Bhagawadgita, science is said to be an aspect of Wijnana, namely an aspect of knowledge that develops human intelligence. , which emphasizes the health and perfection of the soul, so that it returns to the source of the soul (God). 2. Teachings of Samadhi Yoga as Ethical Education for Wiku. A priest, even though his spiritual education is very high, but if he does not adhere to the ethical teachings of his priesthood, he is nothing more than a criminal who is spiritual. There are a lot of lontars that talk about ethics education for the wiku, for example Ciwa sasana, Silakrama, Rwa compassion vrataning the wiku and including the Lontar Samadhi Yoga Gegelaran wiku. In Wiku's Lontar Samadhi Yoga event, great emphasis is placed on the ethics of eating. The wiku is not allowed to eat like a walaka, because that food will affect the existence of a priest. The teachings of Samadhi Yoga as a means to form a complete human being.